Colombian Rasch validation of KIDSCREEN27 quality of life questionnaire (2016)
ABSTRACT: Background: The family of KIDSCREEN instruments is the only one with trans-cultural adaptation and validation in Colombia. These validations have been performed from the classical test theory approach, which has evidenced satisfactory psychometric properties. The aim of this study was to evaluate psychometric properties of KIDSCREEN-27 children and parent-proxy versions, through Rasch analysis. Methods: The participants in the present study were two different sets of populations, 321 kids with a mean age of 12.3 (SD 2.6), 41 % 8 to 11 years old and 59 % 12 to 18 years old; and 1150 parent-proxy with an average age of 45.5 (SD 18.9). Psychometric properties were assessed using the partial credits model in the Rasch approach. Unidimensionality, fitting of person and item, response form, and differential item functioning (DIF) were measured. Results: The Infit MNSQ in child self-reported version that ranges between 0.71–1.76, and 0.69–1.31 in the parent-proxy version. Scores gathered on Likert forms of 5-response options, person separation was 2.08 for child self-reported version and 2.40 for parent-proxy; reliability was 0.81 and 0.85, respectively. Items reliability was 0.99 on both versions, with separations of 11.92 for child self-reported and 10.83 for parent-proxy. There was not DIF according to the variables sex and age but was present according to socioeconomic status. Conclusion: There was a good fit for items and individuals to the Rasch model. Item separation was adecuate, and person separation improved when the response form was re-codified to four options. The presence of DIF according to socioeconomic status implies a scale’s bias in the measure of HRQoL of Colombian children.